2012
DOI: 10.1016/j.ijer.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond subject boundaries: Four case studies of cross-curricular pedagogy in secondary schools

Abstract: Cross-curricularity can be an integral part of an individual teacher's pedagogy; Subject links within cross-curricular practices are complex and multi-levelled; Analysis of cross-curricular pedagogies should acknowledge broader contexts; Curriculum development and teacher development are inextricably linked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Research has previously demonstrated the benefit of cross-curriculum integration, with students understanding the significance of learned knowledge as critical to their overall performance. [64][65][66] Integrating FL concepts with co-subjects, such as mathematics or science, is important for teacher engagement, sustainability, and meaningful acquisition of assets, and to overcome barriers associated with FL education within schools, such as limited time, few resources, and administrative burden. 64,67 Study investigators frequently discussed using creative activities, such as imaginative play, art, music, dance, and theater, in FL interventions, particularly those targeted at K-2 students.…”
Section: Discussionmentioning
confidence: 99%
“…Research has previously demonstrated the benefit of cross-curriculum integration, with students understanding the significance of learned knowledge as critical to their overall performance. [64][65][66] Integrating FL concepts with co-subjects, such as mathematics or science, is important for teacher engagement, sustainability, and meaningful acquisition of assets, and to overcome barriers associated with FL education within schools, such as limited time, few resources, and administrative burden. 64,67 Study investigators frequently discussed using creative activities, such as imaginative play, art, music, dance, and theater, in FL interventions, particularly those targeted at K-2 students.…”
Section: Discussionmentioning
confidence: 99%
“…As concluded by Brown (2012, p. 10) there is a drastic lack of "large studies analysing student performance and engagement in K-12 classrooms". Roehrig et al (2012) and Savage (2012) both emphasised that the lack of guidelines and models on how to implement such a program is one of the greatest challenges facing K-12 STEM education.…”
Section: Stem Stem Etcmentioning
confidence: 99%
“…The phrase "STEM education" is used to describe a focus on the teaching of, and the learning within Science, Technology, Engineering, and Mathematics (STEM) fields (Gonzalez & Kuenzi, 2012). A focus on STEM rose to prominence in the US educational arena in response to the ongoing low performance of American students in mathematics and science on international assessments, such as TIMSS and PISA (Breiner, Harkness, Johnson, & Koheler, 2012;Gonzalez & Kuenzi, 2012;Klein, 2008;Marinova & McGrath, 2004;McClam & Flores-Scott, 2012;Roehrig, Moore, Wang, & Park, 2012;Savage, 2012;Wang, Moore, Roehrig, & Park, 2011). Many other countries faced similar challenges and placed an importance on STEM linked subjects within their educational framework (Corlu, Capraro, & Capraro, 2014;Scholz, Lang, Wiek, Walter, & Stauffacher, 2006;Yakman & Lee, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composing music for an advertisement or creating music to accompany a film is are also a popular activitiesprojects for students of this age (Gall Lazarus, Tidmarsh, & Breezeet al, 2009). However, in England, aside from projects that I have heard read about in journal articles (Baxter, 2013;Savage & Challis, 2001Challis, 2007;Savage, 2012;Savage & Butcher, 2007;Savage & Challis, 2001, 2002Savage, 2012Baxter, 2013), I have seen very limited use of technologies for creative activities with 11-to 14 14-year year-olds other than paired work at computer workstations using sequencing or sample-sequencing software. That this is a national issue is confirmed by the latest triennial government music report, that which suggests that technology should be better used "to promote Whilest the use of computers with 11-14 year olds11-to 14-year-olds has not been widespread in English schools, other technologies have become more commonplace: at the turn of the century, the development of Musical Futures, a new pedagogical approach to musical teaching and learning in schools, has led to a wider use of electric guitars and drum kits/pads in the classroom.…”
Section: Music and Information Communications Technology Ict In Englimentioning
confidence: 99%